The Reality of Financing Startups in Algeria Through Provided Support Mechanisms - Ghedifa , Khaled; yamani , leila (Journal of Research in Finance and Accounting, 2025)
This study aims to explore the reality of startups in Algeria according to the support mechanisms offered by the state. The research paper relies on a descriptive analytical approach to describe the variables of the study and analyze and interpret the reality of these enterprises. The findings indicate that the concept of startups in Algeria is relatively new. The Algerian legislator has not provided a definition for startups but has instead outlined related criteria without restricting these enterprises' activities to the technological and innovative fields. There is a significant lack of media and advertising concerning startups, given that this type of enterprise is still in the stages of definition and establishment. The researcher recommends the need to develop and diversify the various mechanisms and support devices for young people, such as business incubators and nurseries, and to link universities with economic institutions. Furthermore, the role of scientific research laboratories in developing entrepreneurial thinking and benefiting from Arab and global ideas, methods, and models specialized in accompanying and establishing micro-enterprises should be activated.